Quantifying gadolinium-based nanoparticle uptake distributions in brain metastases via magnetic resonance imaging - Stephanie Bennett; Camille Verry; Evangelia Kaza; Xin Miao; Sandrine Dufort; Fabien Boux; Yannick Crémillieux; Olivier de Beaumont; Géraldine Le Duc; Ross Berbeco; Atchar Sudhyadhom (Scientific Reports)
Abstract AGuIX, a novel gadolinium-based nanoparticle, has been deployed in a pioneering double-blinded Phase II clinical trial aiming to assess its efficacy in enhancing radiotherapy for tumor treatment. This paper moves towards this goal by analyzing AGuIX uptake patterns in 23 patients. A phantom was designed to establish the relationship between AGuIX concentration and longitudinal ( $${T}_{1}$$ T 1 ) relaxation. A 3T MRI and MP2RAGE sequence were used to generate patient $${T}_{1}$$ T 1 maps. AGuIX uptake in tumors was determined based on longitudinal relaxivity. AGuIX (or placebo) was administered to 23 patients intravenously at 100 mg/kg 1–5 hours pre-imaging. Each of 129 brain metastases across 23 patients were captured in $${T}_{1}$$ T 1 maps and examined for AGuIX uptake and distribution. Inferred AGuIX recipients had average tumor uptakes between 0.012 and 0.17 mg/ml, with a mean of 0.055 mg/ml. Suspected placebo recipients appeared to have no appreciable uptake. Tumors presented with varying spatial AGuIX uptake distributions, suspected to be related to differences in accumulation time and patient-specific bioaccumulation factors. This research demonstrates AGuIX's ability to accumulate in brain metastases, with quantifiable uptake via $${T}_{1}$$ T 1 mapping. Future analyses will extend these methods to complete clinical trial data (~ 134 patients) to evaluate the potential relationship between nanoparticle uptake and possible tumor response following radiotherapy. Clinical Trial Registration Number: NCT04899908. Clinical Trial Registration Date: 25/05/2021.